2013
DOI: 10.1042/bst20120254
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in the circulation: are erythrocyte microvesicles a confounder in the plasma haemoglobin assay?

Abstract: Blood contains a mixture of extracellular vesicles from different cell types, primarily platelets, endothelial cells, leucocytes and erythrocytes. Erythrocytes are the most abundant cell type in blood and could, especially in certain pathologies, represent an important source of vesicles. Since erythrocytes contain the haemoglobin components iron and haem, which are potentially toxic, it is important to investigate the contribution of vesicle-associated haemoglobin to total cell-free haemoglobin levels. To our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Blood contains a variety of extracellular vesicles released from many different cell types, above all platelets, leukocytes, erythrocytes, and endothelial cells (33). To identify the contribution of GBM-derived extracellular vesicles to the whole circulating extracellular vesicle population, we measured extracellular vesicle concentration in paired pre-and postoperative GBM plasma samples (n ¼ 14).…”
Section: Tumor Cells Are Mainly Responsible For Extracellular Vesiclementioning
confidence: 99%
“…Blood contains a variety of extracellular vesicles released from many different cell types, above all platelets, leukocytes, erythrocytes, and endothelial cells (33). To identify the contribution of GBM-derived extracellular vesicles to the whole circulating extracellular vesicle population, we measured extracellular vesicle concentration in paired pre-and postoperative GBM plasma samples (n ¼ 14).…”
Section: Tumor Cells Are Mainly Responsible For Extracellular Vesiclementioning
confidence: 99%
“…Research by others have demonstrated that exosomes (∼50 nm) and microvesicles (∼200 nm) from endothelial cells, leukocytes, and platelets exceed the amount of RBC EVs (i.e., microvesicles) in the plasma of healthy individuals (blood donors) [25] as well as in blood bank-produced RCCs as they enter storage [26]. While we did not look at non-RBC EVs in this study, this prior work led us to postulate that the average size increase of the RCC EVs during storage reflected the accumulation of RBC EVs (microvesicles) over exosomes (non-RBC origin) caused by the RBC vesiculation.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in 1983, two independent groups reported the release of extracellular vesicles by exocytosis of multivesicular endosomes during the maturation of reticulocytes (Harding et al, 1983; Pan and Johnstone, 1983). Although reticulocytes, or immature RBCs, secrete exosomes during the remodeling process that accompanies their maturation, mature RBCs are probably the only cells that do not secrete exosomes and shed only microvesicles (de Vooght et al, 2013). …”
Section: Introductionmentioning
confidence: 99%